Aktivitas Antioksidan Ekstrak Etanol Daun Ganitri (Elaeocarpus Ganitrus Roxb.) dengan Metode DPPH (2,2 Difenil-1-Pikrilhidazil) - Naelaz Zukhruf Wakhidatul Kiromah; Sadam Husein; Titi Pudji Rahayu (Pharmacon: Jurnal Farmasi Indonesia, 2021)
Free radicals are one of the cause of various diseases. The use of synthetic antioxidant compounds could prevent the effect of the free radicals, however may cause adverse effects on the human body such as impaired liver, lung, intestinal and poisoning. Therefore antioxidant from natural resources needs to be developed. The purpose of this research was to determine the antioxidant activity and IC50 value of the ethanol extract of ganitri (Elaeocarpus ganitrus Roxbs.) leaves. Ganitri leaf ethanol extract activity test was carried out using DPPH method with vitamin C as a standard. Antioxidant activity was determined as a decreas in the absorbance of DPPH at 517 nm wavelength after an addition of the extract with the concentrations of 20, 40, 80, and 100 ppm. The antioxidant acitivity measurement of the ganitri leaf extract showed that the linier regression equation obtained was y = 0.3669x + 29.546, r = 0.4573 while the IC50 value was 54,12 ppm. Based on the result, it is concluded that the ethanol extract of ganitri (Elaeocarpus ganitrus Roxb.) leaf showed was categorized as strong antioxidant.